Opportunities and Challenges of Zakat for Economic Equality in Indonesia - Listy Astutiningtyas; Iis Faridah (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2026)
The Economic inequality in Indonesia is caused by the unequal distribution of income and wealth, as measured by the Gini Index. In 2024, it was 0.37 and in 2025, it was 0.38, indicating that inequality is on the rise, with a wide gap between the rich and the poor. Indonesia is a Muslim country where zakat distribution plays a crucial role in economic equality. The implementation of professionally managed zakat in Indonesia has shown positive results in reducing poverty and narrowing income inequality (Gini Index), primarily through productive zakat programs. This success depends heavily on optimizing the national zakat potential and strengthening synergies between amil institutions, the government, and the community.